THE ROLE OF THE SCHOOL PRINCIPAL IN REALIZING GOOD SCHOOL GOVERNANCE AT SDN 007 MAMAHAK BESAR, MAHAKAM ULU REGENCY: A POLICY IMPLEMENTATION STUDY OF PERMENDIKDASMEN NO. 7 OF 2025 - Monika Hagin; Praptiningsih Sukowati; Saudah (PT. Antis International Publisher, 2026)
Objective: This study aimed to analyze the principal’s role in implementing Good School Governance (GSG) and identify its supporting and inhibiting factors following the implementation of the Regulation of the Minister of Primary and Secondary Education No. 7 of 2025. Method: Employing a descriptive qualitative design at SDN 007 Mamahak Besar in Mahakam Ulu Regency, data were gathered through in-depth interviews, field observations, and document analysis involving the principal, teachers, parents, committee members, and supervisors, and analyzed through data reduction, data display, and conclusion drawing. Result: The findings indicate that the principal effectively executes multidimensional roles—as a leader, manager, facilitator, supervisor, decision-maker, and community liaison—enhancing GSG through operational transparency, budget accountability, stakeholder participation, resource efficiency, and responsiveness, although full implementation remains constrained by severe geographical isolation, limited infrastructure, unstable internet connectivity, and administrative weaknesses. Novelty: This study provides unique empirical evidence on how the newly enacted 2025 national leadership regulation is operationalized within a remote and resource-constrained elementary school setting (3T region), bridging the critical gap between centralized education governance policies and the contextual realities of rural educational institutions.